6(9+11v)=

Simple and best practice solution for 6(9+11v)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(9+11v)= equation:


Simplifying
6(9 + 11v) = 0
(9 * 6 + 11v * 6) = 0
(54 + 66v) = 0

Solving
54 + 66v = 0

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-54' to each side of the equation.
54 + -54 + 66v = 0 + -54

Combine like terms: 54 + -54 = 0
0 + 66v = 0 + -54
66v = 0 + -54

Combine like terms: 0 + -54 = -54
66v = -54

Divide each side by '66'.
v = -0.8181818182

Simplifying
v = -0.8181818182

See similar equations:

| -5n-6=7n+6 | | -3(4v-2)+v=4(v+3) | | a-b/9 | | 3u-62=4u-91 | | 6-1y=-2.3 | | 144=12(x-5) | | 80=23-3u | | 5[4x+6]=6x+9 | | -2r+1=-4r+9 | | Y=2r+5 | | 12-a/36=47 | | n+20n=5(n+20) | | 8+2(7u-3)=-2(4u-8)+4u | | 9+2r+3r= | | 36/500 | | 8[3x-4]=4x-2 | | 3(x-1)=7(x-9) | | 3x+7=61 | | 1/3*3.14*10^2*24 | | 3(y+33)=2(y+33) | | 5(2x-8)=3(x-6)-1 | | 4-24/8= | | -4n+7-n=6+4n | | 30=7y-y | | 72=4x+5x | | 6+5(-7x-8)=2 | | 4*(8-4)/2 | | 25=-5(4t-3) | | 3v-12=45 | | (6x+11)=120 | | 3(1+x)+5=3(1+x)-7 | | -5x-13+7x-13=-4 |

Equations solver categories